The benefits of laser scanning and 3D modelling in accident investigation: in a mining context. (May 2015) - Eyre, M. L.; Foster, P. J.; Jobling-Purser, J.; Coggan, J.
Abstract : Accurate reconstruction of the facts and causes surrounding accidents is critical if the mining industry is to learn from incidents and prevent future events. Effective accident investigation and training are essential in order to accomplish this, while providing a record of the incident in order to help in explaining the situation to people unconnected to the event itself. Over a number of years there have been considerable innovations in survey instrumentation and software used to record data. However, the final deliverable data has remained the same, with surveyors tasked to represent a 3D environment using 2D deliverables. This paper explores the benefits that can be obtained using 3D data capture and representation with regard to accident investigation with discussion on accuracy, time, witness verification and reduction in human error.